P3DB: An Integrated Database for Plant Protein Phosphorylation - Yao, Qiuming; Bollinger, Curtis; Gao, Jianjiong; Xu, Dong; Thelen, Jay J. (Frontiers in Plant Science, 2012)
Protein phosphorylation is widely recognized as the most pervasive, enzyme-catalyzed post-translational modification in eukaryotes. In particular, plants have purloined this signaling mechanism as evidenced by the two-fold higher frequency of protein kinases within the genome compared to other eukaryotes. While all aspects of plant protein phosphorylation research have grown in the past ten years; phosphorylation site mapping using high-resolution mass spectrometry has grown exponentially. In Arabidopsis alone there are thousands of experimentally-determined phosphorylation sites. To archive these events in a user-intuitive format we have developed P3DB, The Plant Protein Phosphorylation Database (p3db.org). This database is a repository for plant protein phosphorylation site data, currently hosting information on 32,963 non-redundant sites collated from 23 experimental studies from seven plant species. These data can be queried for a protein-of-interest using an integrated BLAST function to query similar sequences with known phosphorylation sites among the multiple plants currently investigated. Thus, this resource can help identify functionally-conserved phosphorylation sites in plants using a multi-system approach.